Save media! - Benni Setiawan (Universitas Negeri Yogyakarta, 2021)
Print mass media face a big problem. One of them is the decline in subscribers, and the print mass media also loses advertisers. The migration of readers from print to online is not only during a pandemic but has occurred since the last few decades. However, when the Covid-19 pandemic hit, the print media became more difficult. The media reduces production costs by laying off employees. The press also reduced the number of pages to stay afloat in difficult times.